EFEKTIVITAS PROGRAM BINA KELUARGA BALITA PADA ORANG TUA BALITA PENERIMA MANFAAT DI DESA RUGEMUK KECAMATAN PANTAI LABU KABUPATEN DELI SERDANG - Saufa, Ikhwani; Atika, Tuti (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2023)
The development of the quality of human resources will affect national development. The quality of human resources is represented through the quality of health, level of intelligence, emotional and spiritual maturity, and productivity is determined by the quality of children from an early age. In improving the quality of the next generation, the government implements several programs to improve the quality of children from an early age, one of which is carried out by the Office of Women's Empowerment and Child Protection and Population Control and Family Planning (DP3A & P2KB). The program from DP3A & P2KB is BKB (Family Development). Toddlers) which is a policy formulation in the field of family planning aims to increase the knowledge and skills of parents or other family members in caring for, caring for and educating toddlers. In the toddler family development program there are seven aspects of child development parameters in the toddler family development program, namely, gross motor development, fine motor development, passive communication, passive communication, intelligence development, self-help abilities, social behavior. In the toddler family development program there are three activities, namely, counseling, playing APE, and recording the results of the child's growth and development into the child's development card. This study aims to determine the effectiveness of the toddler family development program on beneficiary toddler parents in Rugemuk Village, Pantai Labu District, Deli Serdang Regency. The main informants in this study were members of the toddler family development program, the key informants were the KB coordinator of the Pantai Labu District, as well as additional informants from the toddler family development program cadres. Data collection techniques were carried out by literature study, observation, interviews and documentation. The data obtained in the field were analyzed qualitatively so that it was concluded that the toddler family development program for beneficiary toddler parents in Rugemuk Village, Pantai Labu District, Deli Serdang Regency was effective using four indicators to measure effectiveness namely, program target accuracy, program socialization, program objectives and program monitoring.